2015
DOI: 10.1097/hcr.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Pedometer-Based Telephone Coaching Program on Weight and Physical Activity for People Referred to a Cardiac Rehabilitation Program

Abstract: Participants in the HW group achieved modest improvements in weight, and those in the PA group demonstrated increased physical activity. Low-contact, telephone-based interventions are a feasible means of delivering lifestyle interventions for underserved rural communities, for those not attending cardiac rehabilitation, or as an adjunct to cardiac rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 14 publications
1
64
0
Order By: Relevance
“…These services have shown significant weight loss outcomes (ranging from −1.3 to −5.4 kg over 6 to 12 months) and behaviour change outcomes approximating those reported in the precursor randomised trials [20,[22][23][24]. Such interventions may also be appropriate for the large number of hospital patients identified as requiring outpatient weight management services.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…These services have shown significant weight loss outcomes (ranging from −1.3 to −5.4 kg over 6 to 12 months) and behaviour change outcomes approximating those reported in the precursor randomised trials [20,[22][23][24]. Such interventions may also be appropriate for the large number of hospital patients identified as requiring outpatient weight management services.…”
Section: Introductionmentioning
confidence: 94%
“…Australia [22] and for patients previously hospitalised with coronary heart disease [23]. These services have shown significant weight loss outcomes (ranging from −1.3 to −5.4 kg over 6 to 12 months) and behaviour change outcomes approximating those reported in the precursor randomised trials [20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Per the inclusion criteria for this RE‐AIM review, all interventions took place in rural areas. Seven of the 50 unique interventions (14%) included both rural and urban participants . Publications for all interventions referenced a “rural” setting; however, there was not a consistent definition or approach used across interventions.…”
Section: Resultsmentioning
confidence: 99%
“…In a web‐based program for CAD patients, that included CR participants, participants had a significantly ( p < 0.003) greater weight loss (average of 3.7 vs. 0.47 pounds; Southard, Southard, & Nuckolls, ). Overweight cardiac patients in CR randomised to a pedometer‐based telephone coaching programme had greater weight loss than the physical activity‐only group (Sangster et al, ). Although these studies demonstrated effectiveness, weight losses achieved by participants were not sustained and/or did not reach weight loss of clinical significance.…”
Section: Introductionmentioning
confidence: 99%